2016
DOI: 10.3390/en9110887
|View full text |Cite
|
Sign up to set email alerts
|

Application of a LiFePO4 Battery Energy Storage System to Primary Frequency Control: Simulations and Experimental Results

Abstract: This paper presents an experimental application of LiFePO 4 battery energy storage systems (BESSs) to primary frequency control, currently being performed by Terna, the Italian transmission system operator (TSO). BESS performance in the primary frequency control role was evaluated by means of a simplified electrical-thermal circuit model, taking into account also the BESS auxiliary consumptions, coupled with a cycle-life model, in order to assess the expected life of the BESS. Numerical simulations have been c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 31 publications
(40 reference statements)
2
15
0
2
Order By: Relevance
“…Gatta et al [97,98] evaluated the power consumption of the S-TMS for BESS and showed that the auxiliary consumption through the S-TMS increases with higher system utilization. Rydh et al [99,100] simulated LIB PV-BESS for the calculation of the overall system efficiency by including the auxiliary consumption of the S-TMS and analyzed the impact of different battery operating temperatures.…”
Section: System Thermal Management System (S-tms)mentioning
confidence: 99%
“…Gatta et al [97,98] evaluated the power consumption of the S-TMS for BESS and showed that the auxiliary consumption through the S-TMS increases with higher system utilization. Rydh et al [99,100] simulated LIB PV-BESS for the calculation of the overall system efficiency by including the auxiliary consumption of the S-TMS and analyzed the impact of different battery operating temperatures.…”
Section: System Thermal Management System (S-tms)mentioning
confidence: 99%
“…The main focus of the work in [4], [5], [6], [7], [8], [9] and [10] is on the operational control strategy, including the recharge controller, of a BESS providing frequency control. This control strategy should be designed carefully, as it has an important impact on the required energy content and on the lifetime of the BESS, as shown in [4], [5] and [11].…”
Section: Related Work and Contributionsmentioning
confidence: 99%
“…Specific protocols and regulations have been set by the TSO for the PCR operation and market participation of battery systems [22]. Model-based studies on battery systems providing PCR already evaluated battery lifetime [23,24], sensitivity studies on the energy management strategies and regulations [25], as well as economic implications for the battery system operation [24]. Figure 2 shows a schematic overview of the system under investigation.…”
Section: Second-life Battery Systemmentioning
confidence: 99%